The gut microbiota may be a novel pathogenic mechanism in loosening of orthopedic implants in rats. Issue 11 (15th September 2020) - Moran, Meghan M.; Wilson, Brittany M.; Li, Jun; Engen, Phillip A.; Naqib, Ankur; Green, Stefan J.; Virdi, Amarjit S.; Plaas, Anna; Forsyth, Christopher B.; Keshavarzian, Ali; Sumner, Dale R.
Abstract: Particles released from implants cause inflammatory bone loss, which is a key factor in aseptic loosening, the most common reason for joint replacement failure. With the anticipated increased incidence of total joint replacement in the next decade, implant failure will continue to burden patients. The gut microbiome is increasingly recognized as an important factor in bone physiology, however, its role in implant loosening is currently unknown. We tested the hypothesis that implant loosening is associated with changes in the gut microbiota in a preclinical model. When the particle challenge caused local joint inflammation, decreased peri‐implant bone volume, and decreased implant fixation, the gut microbiota was affected. When the particle challenge did not cause this triad of local effects, the gut microbiota was not affected. Our results suggest that cross‐talk between these compartments is a previously unrecognized mechanism of failure following total joint replacement.